Managed floats to damp world-wide exchange rate liquidity shocks like 1982-5, 2006-9: Field and laboratory evidence for the benefits of a single world currency - Robin Pope; Reinhard Selten (The Open Economics Journal, 2011)
This paper's field evidence is: (1) in reality a major exchange rate change devastates an economy, i.e. the widespread academic faith that exchange rate changes are either beneficial or harmless is a false faith that contributes to needless world-wide economic havoc; (2) the 1982-85 exchange rate liquidity crisis sent much of the third world into unmanageable debt levels and was so devastating for the first world that in 1985 the G5 instituted managed cooperating floats; (3) nearly all economists in the official sector and in academe rapidly forgot the devastation and reverted to advocating what caused that devastation, namely a closed economy clean floats exchange rate perspective; and (4) the 2006-2008/9 exchange rate liquidity shock would have been far more drastic but for central bank currency swaps yet the role of these swaps in averting unmanageable exchange rate mayhem that would have precluded the September 2008 rescue of the world financial system, has been ignored. The field evidence thus decisively favours stabilizing managed floats, or better a single world currency, and a means of preventing economists in official sectors and in academe forgetting the devastation and dangers of multiple currencies. This field evidence is bolstered by a laboratory experiment. The experiment incorporates more aspects of real world complexity and more different sorts of official and private sector agents than other investigations and employs a new central bank cooperation-conflict model of exchange rate determination. The experiment allows an interpretation within an umbrella theory of Pope, namely SKAT, the Stages of Knowledge Ahead Theory. Our joint field plus laboratory evidence indicates that official sectors should maintain an international exchange rate oriented perspective as advocated in Davidson 2009 and in the September 2010 Report by UNCTAD, the UN Conference on Trade and Development. But our field evidence details needless fragility in cooperatively managed exchange rate systems. Our joint field plus laboratory evidence thus favours a single world currency, a possibility put on the agenda in March 2009 by Zhou Xiaochuan, head of the People's Bank of China, recommended in July 2009 by the Russian President Dmitry Medvedev, and forwarded as an option in the April 2010 International Monetary Fund Report on Reserve Accumulation and International Monetary Stability. To avoid rapid forgetting of havoc from solationist clean floats and the value of stable exchange rates, indeed better yet a single world currency, a new syllabus, as under the SKAT umbrella, is fundamental. SKAT allows for risk effects including those from (a) difficulties of agents in evaluating alternatives in a complex environment in which the assumed maximization of expected utility is impossible; (b) planning difficulties under uncertainty; and c) the preference for safety and reliability is not trivialized. SKAT contrasts with the current economists' paradigm of expected utility and game theory that lacks a), b) and c) and hence lacks a means for economists to understand that exchange rate uncertainty matters. SKAT is fundamental for the education of official sector members in order to furnish them with a coherent alternative intellectual framework to current university education that excludes liquidity crises and debt costs due to unpredicted exchange rate changes.
Keywords: D80; F31; 330; managed float; IMF; exchange rate regime; experiment; SKAT the stages of knowledge ahead theory; exchange rate shocks; central bank cooperation; central bank conflict; UNCTAD; learning; forgetting; maximizing; expected utility theory